Universal Health Coverage and Litigation in Latin America - Iunes, Roberto; Cubillos-Turriago, Leonardo; Escobar, Maria-Luisa (World Bank, Washington, DC, 2013)
In recent years, several middle-income Latin American countries have seen a steep increase in the number of cases litigating access to curative services and inputs. A renewed judicial approach to the enforcement of the right to health, the expansion of health coverage, a more demanding public interest, an increased prevalence of non communicable diseases and a limited capacity for fair and solid benefit basket design lie at the basis of this phenomenon. Using an interdisciplinary approach and evidence from Argentina, Brazil, Chile, Colombia, Costa Rica, Peru, and Uruguay, this paper examines this complex phenomenon and outlines some of its roots and impacts. It also argues for the need to incorporate a rights-based approach to health policy as a foundation to societal efforts to achieve universal health coverage.